Nilai-Nilai Edukatif Dalam Al-Qur'an Surah Yusuf Ayat 23-29 Tentang Akhlak (Kajian Ilmu Pendidikan Islam) - Raito, Raito; Pangastuti, Sri Anggun (STAI Al-Musaddadiyah Garut, 2024)
Morals are the state of a person's soul that appears on its own. It has a central role in human life in various aspects of life. It involves how individual humans interact with other humans, decide between acting good and bad so as to live life with integrity and high morality. The rapid development and advancement of Science and Technology, apparently affects one's morals in life. As Muslims, we have guidelines that can be used as a basis for life, namely the Qur'an and As-Sunnah. This research aims to describe the educational values ​​in the Al-Qur'an Surah Yusuf Verses 23-29 concerning Morals in the Study of Islamic Education, namely; 1. Educational Values ​​contained in the Al-Qur'an Surah Yusuf verses 23-29, 2. Educational Values ​​contained in the Al-Qur'an Surah Yusuf verses 23-29 concerning Morals in the study of Islamic Education.The method used in this research is to use qualitative research methods. Where according to Bodgan and Taylor, qualitative methodology is a research procedure that produces descriptive data in the form of written or spoken words from people and behavior can be observed. This approach is directed at the setting and the individual as a whole. Based on the results of the study, it can be concluded that the educational values in the Qur'an Surah Yusuf verses 23-29 according to the study of Islamic Education Science are including the value of morals to Allah SWT (in the form of khouf), moral values to oneself (in the form of Iffah) and moral values to others (in the form of Amanah). Keywords: Educational Value, Morals, Q.S Yusuf 23-29, Islamic Education